Nutrient Sensor mTOR and OGT: Orchestrators of Organelle Homeostasis in Pancreatic β-Cells - Nicholas Esch; Seokwon Jo; Mackenzie Moore; Emilyn U. Alejandro (Journal of Diabetes Research)
The purpose of this review is to integrate the role of nutrient-sensing pathways into β-cell organelle dysfunction prompted by nutrient excess during type 2 diabetes (T2D). T2D encompasses chronic hyperglycemia, hyperlipidemia, and inflammation, which each contribute to β-cell failure. These factors can disrupt the function of critical β-cell organelles, namely, the ER, mitochondria, lysosomes, and autophagosomes. Dysfunctional organelles cause defects in insulin synthesis and secretion and activate apoptotic pathways if homeostasis is not restored. In this review, we will focus on mTORC1 and OGT, two major anabolic nutrient sensors with important roles in β-cell physiology. Though acute stimulation of these sensors frequently improves β-cell function and promotes adaptation to cell stress, chronic and sustained activity disturbs organelle homeostasis. mTORC1 and OGT regulate organelle function by influencing the expression and activities of key proteins, enzymes, and transcription factors, as well as by modulating autophagy to influence clearance of defective organelles. In addition, mTORC1 and OGT activity influence islet inflammation during T2D, which can further disrupt organelle and β-cell function. Therapies for T2D that fine-tune the activity of these nutrient sensors have yet to be developed, but the important role of mTORC1 and OGT in organelle homeostasis makes them promising targets to improve β-cell function and survival.